Pengolahan Hasil Budidaya Jamur Tiram pada KWT Keselet Karya di Desa Pringgajurang Utara Kabupaten Lombok Timur - Mulyawati, Sri; Tajidan, F.X. Edy Fernandez; Efendy; Sharfina Nabilah; Muhammad Taufik Kurohman (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Pringgajurang Utara Village is one of the villages located in the Rinjani Geopark area, which is one of the priority locations for research and community service at Mataram University. Pringgajurang Utara Village has a humid climate, making it a breeze to cultivate oyster mushrooms in the area. KWT Keselet Karya is a productive economic group that cultivates oyster mushrooms. The oyster mushroom cultivation yields are quite abundant and are sold directly to buyers without going through any processing. The processing stage is an important aspect of the agricultural product downstreaming programme. However, KWT Keselet Karya does not yet have the knowledge and skills to process oyster mushrooms into more durable products. In addition, there is a problem with human resource management in the KWT, where group members do not clearly understand their duties and functions as part of the group. Therefore, the purpose of this community service is to create innovative processed food products from oyster mushrooms cultivated by KWT Keselet Karya. The methods used include socialisation, training, and mentoring for the community. The object or target of the activity is 25 members of KWT Keselet Karya. The community service activity was carried out at the production house of one of the members, namely in Keselet Hamlet, Pringgajurang Utara Village, Montong Gading District, East Lombok Regency. The results of this community service activity were a significant increase in participants' understanding of oyster mushroom processing and a clear division of tasks among members. The products produced were oyster mushroom chips and nuggets that were ready for sale. The community service outcomes were successfully achieved, namely a clear division of tasks among KWT members and the availability of innovative oyster mushroom products.